Profil Psychological Well-Being pada Siswa Kelas X SMA Negeri 12 Semarang Tahun Pelajaran 2018/2019 - Sugiyo, Sugiyo; Muslikah, Muslikah; Antika, Eni Rindi; Sutikno, Ulung Giri (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Psychological well-being of students is important in the process of continuing effective learning. High school students in the transition from children to adults, various changes that occur such as physical, physiological, cognitive, social and environmental affect their growth and development. Social security increases pressure on students which increases the quality of the psychological well-being of these students. The role of guidance and counseling in schools, improve the psychological well-being of students in schools, including in SMA Negeri 12 Semarang. The purpose of this study was to examine the condition of psychological well-being in SMA Negeri 12 Semarang. The research method uses descriptive quantitative, sampling techniques, simple random sampling totaling 120 students of class X SMA Negeri 12 Semarang. The results showed that 16.7% of students were dependent on the high category, 67.6% of students were dependent on the medium category. While 15.7% is still in the low category. While the t-test results obtained sig. p = 0.316> 0.05 which means there is no significant difference in psychological well-being between male and female student. The conclusion of the study, the level of psychological well-being in class X students of SMA Negeri 12 Semarang is based on the moderate category with a percentage of 67.6% or the number of 68 students and there is no significant difference in the psychological well-being of male and female students